The Implementation of Global Citizenship Education Through Strengthening Circular Economy Values as an Effort to Achieve Sustainable Family Resilience in Sukodermo Village and Kertosari Village, Pasuruan Regency - Abdullah; Satria Akbar Pangestu; Dinar Ayu Sekar Pawening; Cahyo Ilham Firmansyah Subagio; Dano Purba; Yustika Citra Mahendra (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Sukodermo Village and Kertosari Village have abundant natural resource potential. However, behind this abundant potential is a problem of cleanliness, namely the large amount of waste that needs to be appropriately managed. Community service in Sukodermo Village and Kertosari Village aims to instill public awareness of global issues, especially the environment, by strengthening the circular economy as a global action. This service is carried out through a gradual Global Citizenship Education (GCED) approach, including surveys, pre-tests, socialization, training, post-tests, and focus group discussions (FGD). This community service program evaluates the level of community knowledge and interest in various environmental education topics. Pre-test data shows that most participants need more knowledge about Global Citizenship Education (GCED), circular economy, and organic waste management. Furthermore, post-test data shows a significant increase in participant knowledge after the intervention program, where previously, the community only had an understanding level of 10% to 46.7%, increasing to 90% to 96.7%. Finally, the FGD that was conducted successfully produced a collaborative design for all levels of the village to jointly realize a Village that has global awareness and implements a circular economy as an effort to care about environmental issues and improve welfare. Overall, these results show a significant increase in knowledge and interest in implementing environmental education and circular economy programs in Sukodermo Village and Kertosari Village, which can contribute to the development of better environmental education.